Galectin‐3 and risk of cardiovascular events and all‐cause mortality in type 2 diabetes - Tan, Kathryn C.B.; Cheung, Ching‐Lung; Lee, Alan C.H.; Lam, Joanne K.Y.; Wong, Ying; Shiu, Sammy W.M. (Diabetes/metabolism research and reviews, 2019)
Aims Recent clinical studies have shown that galectin‐3 is a prognostic indicator in patients with coronary heart disease and in patients with heart failure. Experimental data suggest that galectin‐3 may play a role in atherogenesis. We have evaluated whether serum galectin‐3 level is associated with cardiovascular outcome in type 2 diabetes. Materials and methods Galectin‐3 was measured in baseline samples in 1495 persons with type 2 diabetes. The primary cardiovascular outcome, incident cardiovascular events, was defined as first non‐fatal myocardial infarction, non‐fatal stroke, coronary revascularization, or death from cardiovascular cause. The secondary outcome was all‐cause mortality. Results At baseline, 12% of the subjects had prevalent cardiovascular disease. Serum galectin‐3 was increased in the group with incident cardiovascular events compared with those who remained free of events during follow up (9.03 ± 2.98 ng/mL vs 8.15 ± 2.76, P < 0.01). Serum galectin‐3 was also significantly increased in those subjects with a fatal outcome. The hazard ratios (HR) for cardiovascular events and all‐cause mortality for individuals in the top quartile were 2.50 (95% CI 1.87, 3.36, P < 0.001) and 3.92 (95%CI 2.55, 6.01, P < 0.001), respectively. In a multivariate Cox regression analysis including traditional risk factors, log (eGFR), baseline albuminuria, and cardiovascular disease status, the HR per standard deviation change in galectin‐3 was 1.13 (95% CI 1.02, 1.26, P = 0.02) for cardiovascular events and 1.17 (95% CI 1.01, 1.35, P = 0.04) for all‐cause mortality. Conclusions Serum galectin‐3 is associated with adverse cardiovascular outcomes in persons with type 2 diabetes independent of traditional risk factors.